Chemical composition of Kelempayan (Neolamarckia Cadamba) - Razak, Athirah; Idrus, Hanis Afiqah; Mohd Noor, Nurul Fahana; Mohd Noor, Siti Nor Fatihah (2012)
The research was carried out to study the chemical composition of Kelempayan (Anthocephalus Chinensis). Kelempayan is the commercial fast growing tree that valuable in wood industry in our country. Sample for the research were taken from the log at breast height of each tree. It is from Rubiaceae family which is ranging from 720 kg/m3 densities and categories as light hardwood. Five experiment was carried out are determination of moisture content, cold-water solubility, hot-water solubility, 1% NaOH solubility of wood and the percentage of ash in wood. The percentage of result shows the content of chemical components in wood such as extractive component, lignin and ash. Besides that, the result also indicates the degree of decay or degradation.